EFFECT AND FREQUENCY OF APPLICATION OF SOME HERBICIDES ON FIELD BIND WEED CONTROL Convolvulus arvensis L. - S .H. Anter (Mesopotamia Journal of Agriculture)
The factorial pots experiment was conducted in order to investigate the effect of some herbicides ( Basagran , 250,500 , Glyphosate , 565 , 1250 , Gesagard , 1250 , 2500 cm3 a.i /ha) and unweeded check treatment which applied with different frequency of application ( one , two , three times )which take 20 days interval on control of fieldbind weed in summer season 2006 at Salah Aldeen prov . CRD design with three replicates was used . The significant result showed that all herbicides used were superiority on plant growth if it compared with unweeded cheek treatment . On other hand , two times or three times duration application of herbicides had more effect on plant length than one time of application . However, unsignificant result of different herbicides frequency had been on number of buds, no-capsule , and no-of seeds .